Thyroid function and epilepsy: a two-sample Mendelian randomization study - Lu, Di; Wang, Yunming; Yang, Yanfeng; Zhang, Huaqiang; Fan, Xiaotong; Chen, Sichang; Wei, Penghu; Shan, Yongzhi; Zhao, Guoguang (Frontiers in Human Neuroscience, 2024)
Background: Thyroid hormones (THs) play a crucial role in regulating various biological processes, particularly the normal development and functioning of the central nervous system (CNS). Epilepsy is a prevalent neurological disorder with multiple etiologies. Further in-depth research on the role of thyroid hormones in epilepsy is warranted. Methods: Genome-wide association study (GWAS) data for thyroid function and epilepsy were obtained from the ThyroidOmics Consortium and the International League Against Epilepsy (ILAE) Consortium cohort, respectively. A total of five indicators of thyroid function and ten types of epilepsy were included in the analysis. Two-sample Mendelian randomization (MR) analyses were conducted to investigate potential causal relations between thyroid functions and various epilepsies. Multiple testing correction was performed using Bonferroni correction. Heterogeneity was calculated with the Cochran's Q statistic test. Horizontal pleiotropy was evaluated by the MR-Egger regression intercept. The sensitivity was also examined by leave-one-out strategy. Results: The findings indicated the absence of any causal relationship between abnormalities in thyroid hormone and various types of epilepsy. The study analyzed the odds ratio (OR) between thyroid hormones and various types of epilepsy in five scenarios, including free thyroxine (FT4) on focal epilepsy with hippocampal sclerosis (IVW, OR= 0.9838, p=0.02223), hyperthyroidism on juvenile absence epilepsy (IVW, OR= 0.9952, p= 0.03777), hypothyroidism on focal epilepsy with hippocampal sclerosis (IVW, OR= 1.0075, p= 0.01951), autoimmune thyroid diseases (AITDs) on generalized epilepsy in all documented cases (weighted mode, OR= 1.0846, p= 0.0346) and on childhood absence epilepsy (IVW, OR= 1.0050, p= 0.04555). After Bonferroni correction, none of the above results showed statistically significant differences. Conclusions: This study indicates that there is no causal relationship between thyroid-related disorders and various types of epilepsy. Future research should aim to avoid potential confounding factors that might impact the study.